Ribosomal and Protein Gene Phylogeny Reveals Novel Saprobic Fungal Species From Juglans regia and Urtica dioica - Pem, Dhandevi; Jeewon, Rajesh; Selcuk, Faruk; Ulukapi, Merve; Bhat, Jayarama; Doilom, Mingkwan; Lumyong, Saisamorn; Hyde, Kevin D. (Frontiers in Microbiology, 2020)
During an ongoing investigation of Ascomycetes from plant substrates, three saprobic species were found from plant substrates. Two new species, Leptosphaeria regiae and Neomicrosphaeropsis juglandis were isolated from dead branches of Juglans regia from Turkey. Another species is introduced herein as Subplenodomus urticae sp. nov within the family Leptosphaeriaceae found on Urtica dioica in Italy. Multigene phylogenies based on combined LSU, ITS, SSU and β-tubulin DNA sequence data generated from maximum likelihood and MrBayes analyses indicate that Leptosphaeria regiae is closely related to L. slovacica and L. pedicularis and forms an independent lineage within the genus Leptosphaeria. Subplenodomus urticae is basal to S. iridicola and its establishment as a new species is strongly supported. Neomicrosphaeropsis juglandis forms a moderately supported lineage in between N. italica and N. minima in the Didymellaceae. Full morphological details are provided herein and phylogenetic relationships of the three new species are also discussed.